2003
DOI: 10.1007/s00246-003-0495-2
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Atresia with Intact Ventricular Septum and Major Aortopulmonary Collaterals: Association with Deletion 22q11.2

Abstract: We describe the first association of pulmonary atresia, intact ventricular septum, and absent central pulmonary arteries with deletion 22q11.2. The pulmonary blood flow was derived from major aortopulmonary collaterals. The role of the deletion in pulmonary arborization is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…With confluent pulmonary arteries, significant MAPCAs do not typically develop. This is reflected by few reports of such cases [4,[9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…With confluent pulmonary arteries, significant MAPCAs do not typically develop. This is reflected by few reports of such cases [4,[9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, however, there is but a single case reported of supply through collateral arteries in association with deletion of 22q11.2 when pulmonary atresia is found in the setting of an intact ventricular septum. 4 We describe here a child with pulmonary atresia and 22q11.2 deletion syndrome with confluent branch pulmonary arteries, emphasising the significance of considering the possible association of 22q11.2 deletion syndrome in patients with pulmonary atresia with intact ventricular septum.…”
Section: P Ulmonary Atresia With Intact Ventricularmentioning
confidence: 88%
“…In a review of reported cardiovascular anomalies in chromosome 22q11.2 deletion syndrome, however, 9 pulmonary atresia in the setting of an intact ventricular septum had not been encountered. Indeed, our review of the English literature yielded but a solitary case report 4 describing 22q11.2 deletion in a patient with pulmonary atresia in the setting of intact ventricular septum.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study analyzing the frequency of different types of CHD in consanguineous marriages did not find an association of consanguinity with pulmonary atresia [Khalid et al, 2006]. In further support of a genetic basis, however, four previous single case reports have documented different chromosomal abnormalities in patients with PA-IVS, including trisomy 18 [Patel et al, 1999], 46,XX,t(6;8)(p21.2;q11.2) [Frober et al, 2001], mos47,XX,þi(5p)/46,XX [Paulick et al, 2004] and 46,XY.ish del(22)(q11.2) [Li et al, 2003]. PA-IVS has also been found with an increased frequency in patients with homozygous C677T methylenetetrahydrofolate reductase mutations [Lee et al, 2005], which suggests a genetic basis at least in some cases.…”
mentioning
confidence: 95%